Lipids from the purple and white açaí (Euterpe oleracea Mart) varieties: nutritional, functional, and physicochemical properties - Santos, Orquídea Vasconcelos; Lemos, Yasmin Silva; da Conceição, Leyvison Rafael Viera; Teixeira-Costa, Bárbara E. (Frontiers in Nutrition, 2024)
The Brazilian superfruit called Açaí or Assaí has gained interested from researcher and consumers worldwide, due to its health-related properties. In this context, this pioneering study aimed to compare the physicochemical, nutritional, and thermal properties of vegetable oils obtained from two varieties of açaí (Euterpe oleracea), purple and white. Both açaí oils from white (WAO) and purple (PAO) varieties were obtained by using the conventional solid–liquid extraction, which resulted in oil yields ranging from 52 to 61%. WAO and PAO were analyzed by their edibility quality parameters given the recommendations from Codex Alimentarius; their nutritional functionality indices and their composition of fatty acids and triglycerides content were estimated. Both oils showed low levels of acidity and peroxides, <1.8 mg KOH g−1 and < 1.7 mEq kg−1, respectively, which are good indicators of their preservation status, agreeing with the food regulations. PAO and WAO showed differences among the composition of fatty acids, mainly related to the content of monounsaturated fatty acids (MUFAs), which were 62.5 and 39.5%, respectively, mainly oleic acid. Regarding the polyunsaturated fatty acids (PUFAs), the WAO showed up to 23% of linoleic acid, whereas the PAO exhibited up to 11% of it. These differences reflect on the values of the nutritional functionality indices, atherogenic (AI), thrombogenic (IT), and hypocholesterolemic/hypercholesterolemic ratio (H/H). Both PAO and WAO showed low levels of AI and TI and superior values of H/H than other oilseeds from the literature. These results indicate the nutritional properties of açaí oils regarding a potential cardioprotective effect when included in a regular dietary intake. The thermogravimetric behavior and the evaluation of oxidation status by infrared spectroscopy (FTIR) were also studied. Both açaí oils demonstrated higher thermal stability (with an onset temperature ranging from 344 to 350 °C) and low indications of oxidation status, as no chemical groups related to it were noted in the FTIR spectrum, which agrees with the determined acidity and peroxide content. Moreover, the FTIR analysis unveiled characteristic chemical groups related to fatty acids and triglycerides, agreeing with the literature reports. These findings collectively contribute to a deeper comprehension of the nutritional and functional properties between white and purple açaí oils, offering valuable insights into their potential health, food, and industrial applications.